2011
DOI: 10.4025/actascianimsci.v33i1.9281
|View full text |Cite
|
Sign up to set email alerts
|

Cloridrato de ractopamina em dietas para suínos em terminação

Abstract: RESUMO.O presente trabalho objetivou avaliar o uso de ractopamina em diferentes níveis de inclusão na dieta para suínos em terminação. Foram utilizados 50 suínos híbridos comerciais com peso inicial de 74,08 (1,42) kg, aleatoriamente distribuídos em cinco blocos casualizados. Havia dois animais em cada parcela experimental, macho e fêmea, alimentados com dieta suplementada com ractopamina (0, 5, 10, 15 e 20 ppm) durante 28 dias. Foram avaliados desempenho e características de carcaça dos animais. A ractopamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 26 publications
0
17
0
6
Order By: Relevance
“…Haji-Abadi et al, 2010). The effects of ractopamine on the composition of the fillets can be explained by the activation of β-adrenergic receptors, leading to the activation of hormonesensitive lipase by phosphorylation, thus initiating lipolysis in adipocytes (Mersmann, 2002;Ferreira et al, 2011). In response to this lipolysis, fatty acids are released for use as an energy source in other tissues (Mersmann, 2002;Salem et al, 2006;Haji-Abadi et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haji-Abadi et al, 2010). The effects of ractopamine on the composition of the fillets can be explained by the activation of β-adrenergic receptors, leading to the activation of hormonesensitive lipase by phosphorylation, thus initiating lipolysis in adipocytes (Mersmann, 2002;Ferreira et al, 2011). In response to this lipolysis, fatty acids are released for use as an energy source in other tissues (Mersmann, 2002;Salem et al, 2006;Haji-Abadi et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed a reduction in the fat content with 10 ppm of ractopamine, while 40 ppm increased the fat content compared to the control group, similar to what was observed in the present work. At high levels of ractopamine, it is believed that desensitisation of adrenergic receptors may occur (Ferreira et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…O consumo de ração médio diário (CRMD) não foi influenciado pelos níveis de ractopamina adicionados nas dietas. Bridi et al (2008), Ferreira et al (2011), Garbossa (2013 e Marinho et al (2007b), estudando a ractopamina em dietas para suínos em terminação, também observaram que este aditivo não afetou o consumo. O consumo de ração médio diário por suínos depende do nível energético da ração e, como todas as rações foram isocalóricas, já era esperado um consumo de ração médio diário semelhante.…”
Section: Methodsunclassified
“…Vários trabalhos indicam que as modificações metabólicas proporcionadas pela utilização da ractopamina na dieta melhoram de forma significativa o desempenho desses animais (ARMSTRONG et al 2004;BRIDI et al, 2008;KIEFER & SANCHES, 2009;SANCHES et al, 2010a, FERREIRA et al, 2011, além de proporcionar redução na espessura de toucinho e aumento na porcentagem de carne magra e rendimento de carcaça (KIEFER & SANCHES, 2009). Em grande parte das pesquisas realizadas, até o momento, com suínos, os níveis de ractopamina utilizados situam-se entre cinco e 20 ppm, com níveis variando a cada cinco unidades (STOLLER et al 2003;ARMSTRONG et al 2004;WEBER et al, 2006;BRIDI et al, 2008;CANTARELI et al, 2009;KIEFER & SANCHES, 2009;SANCHES et al, 2010a;FERREIRA et al, 2011), o que causa algumas discrepâncias nos resultados, que vão desde um maior ganho de peso, menor consumo de ração, maior rendimento de carcaça e melhor conversão alimentar, até uma ausência total de efeitos. Torna-se necessário, portanto, fracionar os níveis já listados, cinco a 20ppm, sobretudo no intervalo de cinco a 15ppm, em que a ractopamina mostrouse mais eficiente.…”
Section: Introductionunclassified
“…Despite the dose in the present study being considered low, the evaluation of the cumulative effects of increasing administration periods was a primary aim. The 5 ppm dosage was based on the previous work (Ferreira et al 2011) with the pigs, where authors estimated the optimal value for the RAC treatment between 4.09 and 5.14 ppm, promoting a 6.09% increase in the bonus index, an economic variable related to benefits to the producers for leaner carcasses. Exposure to stress promoted significant changes in the animal growth and relative viscera's weights.…”
Section: Discussionmentioning
confidence: 99%